Discrete mathematics - Epp, Susanna S. (Singapore : Cengage Learning Asia Pte Ltd, 2012)
This book describes processes that consist of a sequence of individual steps. This contrasts with calculus, which describes processes that change in a continuous fashion.
Chapter 1. Speaking Mathematically -- Chapter 2. The Logic of Compound Statements -- Chapter 3. The Logic of Quantified Statements -- Chapter 4. Set Theory -- Chapter 5. Functions -- Chapter 6. Relations.
Keywords: MATHEMATICS